A Review on Non-Linear Programming and Generalized Invexity (Global Journal of Computer Science and Technology, 2014)
Over past few years the concept of NLPP and their related results based on generalized invexity has become one of the prominent and important areas of classical optimization This paper presents a brief review on such problems and their respective results in game theory continuous time programming multivariable optimization composite programming etc
Keywords: non-linear programming; invexity; optimality; duality